Dysembryoplastic neuroepithelial tumor originally diagnosed as astrocytoma and oligodendroglioma - Diego Cassol Dozza; Flávio Freinkel Rodrigues; Leila Chimelli (Arquivos de Neuro-Psiquiatria)
Dysembryoplastic neuroepithelial tumor (DNT), described in 1988 and introduced in the WHO classification in 1993, affects predominantly children or young adults causing intractable complex partial seizures. Since it is benign and treated with surgical resection, its recognition is important. It has similarities with low-grade gliomas and gangliogliomas, which may recur and become malignant. OBJECTIVES: To investigate whether DNT was previously diagnosed as astrocytoma, oligodendroglioma, or ganglioglioma and to determine its frequency in a series of low-grade glial/glio-neuronal tumors. METHODS: Clinical, radiological, and histological aspects of 58 tumors operated from 1978 to 2008, classified as astrocytomas (32, including 8 pilocytic), oligodendrogliomas (12), gangliogliomas (7), and DNT (7), were reviewed. RESULTS: Four new DNT, one operated before 1993, previously classified as astrocytoma (3) and oligodendroglioma (1), were identified. One DNT diagnosed in 2002 was classified once more as angiocentric glioma. Therefore, 10 DNT (17.2%) were identified. CONCLUSIONS: Clinical-radiological and histopathological correlations have contributed to diagnose the DNT.